A Retrospective analysis of Spondyloarthropathies at the Rheumatic Diseases Unit, University of Cape Town, over the period 1988-1994 - Burch, Vanessa Celeste; Burch, Vanessa Celeste (Division of Rheumatology, 2017)
OBJECTIVES: Given the paucity of epidemiological and clinical data representing the South African experience with the spondyloarthropathies, a study was designed to achieve a description of the spectrum of spondyloarthropathy in patients of different ethnic origin attending the Rheumatic Diseases Unit (RDU), University of Cape Town (UCT), in respect of differences in: clinical and/or radiographic expression of disease; gender HLA-B27 status, and choice of therapy and requirements for reconstructive orthopaedic surgical procedures. STUDY DESIGN: The study comprised a retrospective descriptive review of all new cases of spondyloarthropathy seen at the RDU, UCT Medical School, from 1 January 1988 to 31 December 1994, who were consecutively identified from an analysis of the clinical records. The RDU (UCT) is one of two principal referral centres for rheumatic-related diseases in the Western Cape region, and provides clinical services at Groote Schuur Hospital (GSH, Observatory) and Princess Alice Orthopaedic Hospital (PAOH, Retreat) in Cape Town for an estimated population of 3. 4 million (Western Cape), 55% (1.9 million) of whom are resident in the Cape Peninsula region (81). A minority of patients from further afield (Northern Cape and Eastern Cape) also attend the unit. Approximately 12 500 patients attend PAOH outpatient Department (OPD) annually, of which 35% are seen by the RDU staff each year (average values calculated from attendance registers for the period 1 January 1988 to 31 December 1994). New patients constitute about 6% of all patients seen by the RDU per annum (Table 2). Statistical data were not available from the OPD Arthritis Clinic (AC) at GSH, but similar proportions would be expected, since both clinics are staffed by the same complement of doctors and operate under similar circumstances at both venues.